The burden of chronic kidney disease attributable to high sodium intake: a longitudinal study in 1990–2019 in China - Shen, Yongyao; Jiang, Liying; Yu, Jin; Chen, Bo; Liu, Aidong; Guo, Yongjin (Frontiers in Nutrition, 2025)
ObjectiveElevated sodium consumption is associated with increased risk for chronic kidney disease (CKD) and data for this disease burden attributable to high sodium intake in China from 1990 to 2019 are scarce in China. Our study aims to estimate and present the national burden of CKD attributable to high sodium intake, as well as its profile.MethodsThe regional disease burden data from the China Center for Food Safety Risk Assessment (CFSA) from 1990 to 2019 were compiled based on the methodology of GBD 2019. CKD burden [deaths and disability-adjusted life years (DALYs)] was quantified according to population group (age, gender) and regions categories (province, SDI). The estimated annual percentage change (EAPC) in age-standardized mortality rate (ASMR) and age-standardized DALYs rate (ASDR) were calculated to describe long-term trends.ResultsTotally, the number of deaths of CKD attributable to high sodium intake reached 95,000, with DALYs amounting to 2.59 million person-years in 2019, while the trends of ASMR (EAPC: -0.31, 95%CI: −0.46, −0.17%) and ASDR (−0.33, 95%CI: −0.48, −0.18%) were down during the observation period. The age-specific numbers and rates of deaths, as well as DALYs increase with age are higher in males than in females. Significant disparities in CKD burden attributable to high sodium intake were observed across provinces and SDI regions. In both 1990 and 2019, the number of deaths and DALYs were higher in middle SDI regions, while low-middle SDI regions had highest ASMR and ASDR. The EAPC of ASDR was found to be significantly negatively correlated with the 1990 ASDR (ρ = −0.393, p = 0.024), and the EAPC of ASMR and ASDR were also significantly negatively correlated with the 2019 SDI (ASMR:ρ = −0.571, p < 0.001; ASDR:ρ = −0.368, p = 0.035).ConclusionHigh sodium intake accounted for a sizeable burden of disease from 1990 to 2019 in China, also presents sexual and geographic variations. Despite a slight decreasing trend exists, the absolute number increased as much as twofold, particularly among males and seniors. Targeting to reduce sodium intake remains a priority, and progress requires systematic monitoring and evaluation, particularly in middle SDI regions that are experiencing rising trends and low-middle SDI regions being susceptible to approaches.